# Showing that $-\frac{1}{2}=\sum^{\infty}_{n=1}\frac{(-1)^{n}\sin(n)}{n}$

So I've been trying to prove that $$\sum^{\infty}_{n=1}\frac{(-1)^{n}\sin(n)}{n}=-\frac{1}{2}$$

I've tried putting various bounds on it to see if I can "squeeze" out the result. Say something like (one of many tried examples): $$-\frac{1}{n}-\frac{1}{2}\leq \sum^{n}_{k=1}\frac{(-1)^{k}\sin(k)}{k}\leq \frac{1}{n}-\frac{1}{2}$$

I've tried too see if I could find some periodic continuous function in order to use Parseval's theorem, but I can't come up with any that work.

May I please get a hint or some piece of the puzzle for this problem?

Guide:

Verify by computing the fourier series of $$f(x) = \frac{x}{\pi}, -\pi < x<\pi$$

$$\frac{x}{\pi} = \frac{2}{\pi}\sum_{n=1}^\infty \frac{(-1)^{n+1}}{n}\sin(nx)$$

and choose an appropriate value of $$x$$.

• Is there a process for choosing that function? Is it something you just get intuition for? Or is there an obvious reason to choose that function? Oct 9, 2018 at 14:16
• hmmm... unfortunately for my case, it's something that I already know. Oct 10, 2018 at 3:31

A direct approach: $$\sum_{n=1}^\infty\frac{(-1)^n\sin n}n=\sum_{n=1}^\infty\frac{(-1)^n\Im (e^{in})}n=-\Im\sum_{n=1}^\infty\frac{(-1)^{n+1}(e^i)^n}n=-\Im\ln(1+e^i)$$ where the Maclaurin series of $$\ln(1+z)$$ was used. As can be seen by drawing a diagram, $$\arg(1+e^i)=\frac12$$. This is thus the imaginary part of the logarithm, and thus the original sum is $$-\frac12$$.

• The series converges for $|z| < 1$. Why does it converge for $z=e^i$, which has absolute value $1$?
– lhf
Oct 9, 2018 at 14:23
• @lhf you can show that on the boundary the series converges except at $z=-1$. Oct 9, 2018 at 14:24
• @ParclyTaxel One can show this using summation by parts, or more generally by appealing to Dirichlet's test. Oct 9, 2018 at 14:30

Its is also possible to calculate the series above using the residue theorem from complex analysis. It goes as follows:$$\sum_{i=-\infty}^\infty \text{Res}\left(\pi\csc(\pi z)\cdot\frac {\sin(z)}z,n\right)=-\text{Res}\left(\pi\csc(\pi z)\cdot\frac {\sin(z)}z,0\right)$$

The LHS becomes: $$\sum_{i=-\infty}^\infty\lim_{z\to n}\left[\pi (z-n)\csc(\pi z)\cdot\frac {\sin(z)}z\right]=\sum_{i=-\infty}^\infty(-1)^n \frac {\sin(n)}n=2\sum_{i=1}^\infty(-1)^n \frac {\sin(n)}n$$

The RHS becomes: $$\lim_{z\to 0}\left[\pi z\csc(\pi z)\cdot\frac {\sin(z)}z\right]=1$$ Putting all together (LHS $$=-$$ RHS) you get: $$\sum_{i=1}^\infty(-1)^n \frac {\sin(n)}n=-\frac 12$$